To improve health and health care (Jossey-Bass, 2004)
As part of the Robert Wood Johnson Foundation's efforts to inform the public, this book provides an in-depth look into the programs it funds. Suitable for policymakers and practitioners, as well as interested members of the public, it offers lessons for leaders and educators.